Strategi Implementasi Jaminan Kesehatan Nasional dengan Metode Balanced Scoredcard: Studi Kasus di Rumah Sakit X Tangerang Tahun 2018 - Ulandari, Luh Putu Sinthya; Ilyas, Jaslis; Indrayathi, Putu Ayu (UI Scholars Hub, 2020)
One of the private hospital successful implementation the National Health Insurance with cost efficiency without neglecting the quality of service is X Hospital. This study aimed to finding out the strategy of X Hospital in the implementation of the National Health Insurance with Balanced Scorecard. The research was conducted in May 2018 using qualitative approach. Data was collected through in-depth interview to 7 informants from hospital and 2 informants from BPJS Kesehatan. The subjects were selected purposively and the data was analyzed using thematic analysis. The results show that there are several strategies that have been developed and implemented, including: (1) financial perspective (adding types of services, increasing the capacity of inpatients and polyclinics, increasing doctor practice slots, completing medical equipment, applying the principle of low cost and increasing working capital); (2) customer perspective (choosing target market, develop 5 values propotition, complaint management); (3) internal business processes perspective (develop standard operating procedures, develop drug formulary and clinical pathways, carry out operational and audit controls, build business models, form case mix teams and claim management);(4) learning and growth perspective (develop training, giving reward and good salaries, build a competitive work environments, and pay attention to employee career paths). Through this strategy, X Hospital is able to implement the JKN Program well and still record a surplus without sacrificing service quality.